Implementasi Manajemen Kurikulum dan Penilaian dalam Upaya Membentuk Insan Kamil - Rita Sulastini; Sri Handayani; Mugiarto Mugiarto (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2021)
This study aims to describe and analyze the implementation of curriculum management andassessment in an effort to form good people, using qualitative research methods. Sources ofdata in this study are primary sources and secondary sources. Data collection techniques werecarried out by interviews, observation, documentation. Test the validity of the researcher'sdata using credibility, dependability and confirmability. Data analysis includes data reduction,data presentation, drawing conclusions and data collection as a cyclical process. This studydescribes the implementation of curriculum management and assessment at the Ell-FuthahBulupayung Islamic boarding school Patimuan Cilacap in an effort to form good people